Animal snackers - Lewin, Betsy (New York : Henry Holt, 2004)
Short poems describe the eating habits of many different kinds of animals.
Keywords: Animals -- Juvenile poetry; Food habits -- Juvenile poetry; Children's poetry, American; Animals -- Poetry; Food habits -- Poetry; American poetry